Paraneoplastic autoimmunity and small‐cell lung cancer: Neurological and serological accompaniments - Anastasia Zekeridou; Masoud Majed; Ioannis Heliopoulos; Vanda A. Lennon (Thoracic Cancer, 2019)
Paraneoplastic neurological autoimmunity is often associated with small‐cell lung cancer (SCLC), a highly malignant neuroendocrine tumor. Paraneoplastic autoimmunity often correlates with longer survival. We describe the paraneoplastic neurological manifestations of patients with SCLC with and without SCLC‐predictive autoantibodies and the correlation between autoimmunity and survival. We reviewed the records of 116 patients (51% male) from the Mayo Clinic with histopathologically confirmed SCLC for whom stored serum was available for neural autoantibody testing. Cancer was limited stage in 41%; the median age at diagnosis was 64 years. Paraneoplastic neurological manifestations were recorded in 61% (decreasing frequency: peripheral neuropathy, dysautonomia, cognitive decline, cerebellar ataxia, neuromuscular junction disorder, seizures, cranial neuropathy, movement disorder, brainstem disorder, or myelopathy). Neural autoantibodies, some with pathogenic potential, were detected in the sera of SCLC patients with and without neurological autoimmunity. The most frequent among patients with neurological manifestations were: anti‐neuronal nuclear antibody‐type 1, voltage‐gated calcium channel (VGCC)‐N‐type, VGCC‐P/Q‐type, glutamic acid decarboxylase 65 (GAD65), SOX1, and muscle acetylcholine receptor (AChR); while the most common in patients without neurological manifestations were: GAD65, muscle‐AChR, and VGCC‐P/Q‐type. Neither cancer stage at diagnosis nor survival correlated with neurological manifestations or autoantibody‐positivity, except for shorter survival in patients with myelopathy. The only predictor of longer survival was limited‐stage disease at diagnosis.